THE DOMESTIC LIVESTOCK RESOURCES OF TURKEY: NOTES ON DONKEYS - O. Yilmaz; R. Trevor Wilson (Journal of Animal and Plant Sciences, 2013)
Donkeys are an ancient component of Turkey’s domestic animal guild and have been important in the country’s economy for hundreds of years. Turkey is a probable centre of the early use of donkeys in breeding of mules. In 2009 there were almost 300 000 donkeys in the country but numbers are declining rapidly. Three distinct types are catalogued but very little is known about two of them and not much more about the widespread Anatolian type. Turkish donkeys are typical of the world population in morphology and colour and are generally of small size. Donkeys were used by both sides of the conflict in the Great War of 1914-1918. Employed historically as burden and riding animals these roles continue. Use as prime movers and powe sources for agriculture and for wheeled transport is not very widespread but there is some interest in their use for dietic milk. There are no breed societies and no conservation measures in place. Continued downward pressure on numbers (in spite of local increases due to reactions against the cost of mechanized replacements) will continue and will inevitably have a negative effect on an important part of Turkey’s cultural heritage and its domestic animal biodiversity
Keywords: Equus asinus; mule; domestic animal biodiversity; morphology; work animals; coat colour